If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = 2ln(x + 3) Multiply F * x xF = 2ln(x + 3) Reorder the terms: xF = 2ln(3 + x) xF = (3 * 2ln + x * 2ln) xF = (6ln + 2lnx) Solving xF = 6ln + 2lnx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2lnx' to each side of the equation. -2lnx + xF = 6ln + 2lnx + -2lnx Combine like terms: 2lnx + -2lnx = 0 -2lnx + xF = 6ln + 0 -2lnx + xF = 6ln Reorder the terms: -6ln + -2lnx + xF = 6ln + -6ln Combine like terms: 6ln + -6ln = 0 -6ln + -2lnx + xF = 0 The solution to this equation could not be determined.
| -1+8(7-6x)=2x+6 | | 5g-2x=a | | 3L+12=2L+6L+1 | | 4(a+8)+9=12a-9 | | 9=5-4(2x-5) | | 2(k+1)+9=8k-11 | | 10+9(-10-9x)=8-x | | 2(y-5)-7(y)=-15 | | 3(n+10)+11=7n-1 | | 5(b-1)+3(b-1)=4(3-b)+3(4b-2) | | 6(1-2n)=(-3)(n-2) | | x+x+(4*x)+90=180 | | -2-(4-3x)=-7 | | x+x+(4*x)+90=360 | | (-2x-1/3x)×(-9/7x^3y) | | 5x+2.5x+1=55 | | 6(1-2n)=-3(n-2) | | 8x+10x^2-6=17x | | 1-6(2x-3)=-2 | | 5-2(x+2)=9 | | 15x^5+11x^3-14x=0 | | 2x=-32-5(4x-2) | | 5-3(x+2)=9 | | 6(1-2n)=-2(n-2) | | x=y+1-4 | | (9x-8)+(10x+10)= | | Y=x+1-4 | | 4x^2-6x-10-mx-m=0 | | 2.5+10=1.5+17 | | 5x-2(2x+2)=-6 | | 9b-4=1+6(b+11) | | sqrt(6+x)*sqrt(4-x)=3 |